2014
DOI: 10.1242/jeb.096941
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of aDrosophilaFMRFamide in Inducing Muscle Contraction

Abstract: Drosophila melanogaster is a model system for examining the mechanisms of action of neuropeptides. DPKQDFMRFamide was previously shown to induce contractions in Drosophila body wall muscle fibres in a Ca 2+ -dependent manner. The present study examined the possible involvement of a G-protein-coupled receptor and second messengers in mediating this myotropic effect after removal of the central nervous system. DPKQDFMRFamide-induced contractions were reduced by 70% and 90%, respectively, in larvae with reduced e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 71 publications
2
18
0
Order By: Relevance
“…We investigated the most abundant peptide encoded in the Drosophila dFMRF gene, DPKQDFMRFa, which has been isolated and purified from Drosophila tissue and is thought to be released as a neurohormone (Nambu et al 1998;Nichols et al 1999;White et al 1986). Previous work showed that this peptide can increase transmitter release from motor neurons in a cellspecific manner (Dunn and Mercier 2005;Klose et al 2010) and that it acts directly on muscle cells to elicit slow contractions (Clark et al 2008;Milakovic et al 2014). We now present evidence that DPKQDFMRFa alters input resistance preferentially in some muscle cells and elicits stronger contractions in these cells.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…We investigated the most abundant peptide encoded in the Drosophila dFMRF gene, DPKQDFMRFa, which has been isolated and purified from Drosophila tissue and is thought to be released as a neurohormone (Nambu et al 1998;Nichols et al 1999;White et al 1986). Previous work showed that this peptide can increase transmitter release from motor neurons in a cellspecific manner (Dunn and Mercier 2005;Klose et al 2010) and that it acts directly on muscle cells to elicit slow contractions (Clark et al 2008;Milakovic et al 2014). We now present evidence that DPKQDFMRFa alters input resistance preferentially in some muscle cells and elicits stronger contractions in these cells.…”
supporting
confidence: 58%
“…Following dissection, the anterior dissection pin was replaced with the Grass FT03 Force Displacement Transducer (Grass Instrument, Quincy, MA) as described previously (Clark et al 2008;Milakovic et al 2014). Contractions were amplified using a MOD CP122A amplifier (Grass Telefactor, West Warwick, RI), digitized using DATAQ data acquisition (Model DI-145; DATAQ Instruments, Akron, OH), and viewed using WinDaq software (DATAQ Instruments).…”
Section: Force Recordingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proctolin was also shown to reduce octopamine-induced cAMP levels in oviducts, suggesting that the components of octopamine and proctolin signalling pathways interact to modulate oviduct contraction (Nykamp and Lange, 2000). The interaction of RhoprFIRFa and octopamine is not known, although it is not likely that octopamine interacts with the RhoprFIRFa signalling pathway according to a recent study in Drosophila (Milakovic et al, 2014). Milakovic et al (2014) found that FMRFamide-induced muscle contraction is independent of the well-known intracellular players such as calmodulin kinase II, IP 3 , cAMP, etc.…”
Section: Discussionmentioning
confidence: 98%
“…The interaction of RhoprFIRFa and octopamine is not known, although it is not likely that octopamine interacts with the RhoprFIRFa signalling pathway according to a recent study in Drosophila (Milakovic et al, 2014). Milakovic et al (2014) found that FMRFamide-induced muscle contraction is independent of the well-known intracellular players such as calmodulin kinase II, IP 3 , cAMP, etc. ; however, we do not know the pathway used by RhoprFIRFa in this preparation.…”
Section: Discussionmentioning
confidence: 99%